Het Is de schilder happy ? Kunstcollectie Océ '95 - '03. - Haagmans, Fons; Lucker, Louis; Mes, Ulco; Stompff, Guido; Voragen, Thei; van Dun, Ko (Nijmegen : Océ Technlogies b.v., 2003)
Allart, Jeroen ; De Beer, Annemiek ; Berghs, Antoine ; van den Bosch, Mattijs ; Bouchiba, Houcine ; van den Broek, Koen ; Dobbelsteen, Pieter ; Drissen, Paul ; El Karchi, Sidi ; Frieling, Gijs ; Gaba, Meschac ; Gillen, Tina ; Goiris, Geert ; Goossens, Marnix ; Grunschel, Norbert ; Haller Baggesen, Lise ; Hasselaar, Frederika ; Hermans, Benoît ; Hoijmakers, P.H.W. ; Hutsch, Kirsten ; Jonker, Henk ; Kensmil, Iris ; Meerman, Bas ; Meijers, Rik ; Nagtzaam, Marc ; Nijburg, Anke ; Olowska, Paulina ; Van Osch, Maries ; Peltzer, Magdalena ; Raedecker, Michael ; van Riessen, Wouter ; Schuurman, Marike ; Seyen, Peter ; Sman, Raaf Van Der ; Stoner, Tim ; Vermeule, Koen ; Vos, Peter ; Wauman, Wim ; Wiehager, André ; de Wit, Bas ; Zeguers, Alex
Nederlands
Exhibition. Is de schilder happy ? Océ-collectie 1995-2003. Museum van Bommel van Dam Venlo, 14.03.2003 - 11.05.2003.
boek